The Effect of Two Psychological Intervention Programmes on the Improvement of Interpersonal Relationships of Police Officers in Osogbo, Nigeria - Aremu, A. Oyesoji (Criminal justice studies, 2006)
This study investigated the effect of two interactions-Social Skill Training (SST) and Problem-Solving Skills Training (PST)-on police interpersonal relationships. Ninety police officers (whose consents were sought through the Commissioner of Police (CP) Osun State Police Command, Nigeria) participated in the study. Participants who ranged in age between 28 and 47 years (mean = 37.8 years) were randomly and evenly distributed into two experimental and control groups. The interaction effects revealed that participants treated with SST and PST showed significant improvement in their interpersonal relationships. The relative effectiveness of the interaction effects also revealed that the SST was more effective than the PST in the improvement of police interpersonal relationships. These findings were discussed and implications for counselling and police practice stressed.